Evaluasi Kinerja DAS Dan Simulasi Konservasi Menggunakan Swat (Soil And Water Assessment Tool) Studi Kasus : Sub DAS Tapung, Siak, Provinsi Riau) - Mardan Fajri; Manyuk Fauzi; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Alteration of land use which is happening at Tapung watershed (DAS Tapung) is worrying. Marked by the decreasing of forest area from 15.624,36 ha at 2002 to 12.186,32 ha at 2012. Evaluation of watershed condition and performance is needed. Evaluation using (i) Percentage of critical land (PLK) (ii) Percentage of vegetation cover (PPV) (iii) Coefficient regim of flow(KRA) (iv) Coannual of flow (KAT) efficient criteria. Evaluation result of PLK is 9,82%, PPV 71,6%, KRA 14,28 and KAT 0,45. After receiving existing evaluation value, conservation simulation using SWAT program is done by changing a part of open land area and shrub on land use map of 2012 with forest. From simulation result, SWAT model validity parameter R2 is 0,50 and NSE 0,50. These result have satisfied the research objectives as the finding coefficient were > R2 0,4 and >NSE 0,35 From this simulation, watershed condition is evaluated again. Evaluation result after doing conservation simulation are PLK 6,47, PPV 71,6, KRA 5,78, and KAT 0,44. Values after conservation simulation gives better result than the condition before conservation simulation is done.Keywords: altration of land use, SWAT, watershed performance.